Endoscopic findings in uninvestigated dyspepsia patients - K., Thyagaraja; S., Venkatakrishna Bhat; Benny, Stephan (International Journal of Advances in Medicine, 2019)
Background: Dyspepsia is a frequent syndrome in our country where there are limitations for endoscopy and there is high burden of H. pylori infection. It is important to establish the causes of dyspepsia hence therapeutic approach will be easier. Aim of the study was to find out the common endoscopic findings in a patient with dyspepsia symptoms large tertiary care hospital. Methods: A cross-sectional study was conducted on 184 patients either admitted or seen on outpatient basis at the Basaveswara medical college and research institute, Chitradurga with the upper GI symptom dyspepsia and the data was analysed using appropriate statistical methods. Results: Out of 184 patients who underwent Esophagogastroduodenoscopy (EGD scopy) 62% were male and 61% were 31-59year old. The common pathological findings in dyspeptic patients were gastritis and esophagitis. Conclusions: The following insights/observations were made during the course of this study→ dyspepsia is usually caused by H. pylori gastritis, eradication of which relieves the symptom in this observation. Many a times dyspepsia found to have normal study. Hence wise referral for endoscopy is a key in resource limited setup.